Pembelajaran Berdiferensiasi Menggunakan Model Problem Based Learning Serta Pemanfaatan Platform Quizizz Sebagai Asesmen - Nasution, Lukas; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The education sector in Indonesia has entered a new phase. In the wake of the COVID-19 pandemic, the educational paradigm has undergone significant changes. Many activities that were previously conventional have now shifted towards requiring digital platforms to support their processes. One notable change is the integration of digital technology into education. In response to these opportunities and challenges, the author conducts research entitled "Differentiated Learning Using the Problem-Based Learning Model and Utilizing Quizizz Platform as Assessment for Class X Economics at SMA Negeri 3 Samalantan." The aim of this study is to examine how differentiated learning implemented through the problem-based learning model and the use of the Quizizz platform as an assessment tool can be effectively executed, with the expectation that student learning outcomes will improve. The study's population consists of 20 students. Differentiated learning offers new strategies to support the diverse and varied learning development of students. The use of the digital platform Quizizz.com serves as an effective alternative for student assessment. The TPACK (Technological Pedagogical Content Knowledge) approach in teaching greatly assists the researcher, resulting in noticeable success in classroom learning outcomes. The learning results indicate that 15 out of 20 students achieved satisfactory performance. Therefore, it can be concluded that differentiated learning using the PBL model and the Quizizz application can be effectively implemented in teaching practices and improve student learning outcomes.